Characterization of the roles of suppressor of cytokine signaling‐3 in prostate cancer development and progression. Issue 2 (20th April 2015) - Fu, Xian; Ren, Ligang; Chen, Jing; Liao, Kaisen; Fu, Yu; Qian, Xiaoyu; Xiao, Jiaquan
Abstract As negative feedback regulators of cytokine signaling, suppressor of cytokine signaling proteins are induced by interleukins and various peptide hormones and may prevent sustained activation of signaling pathways. In particular, suppressor of cytokine signaling‐3 (SOCS‐3) plays pivotal roles in the development and progression of various cancers and exerts pleiotropic effects on cell proliferation and apoptosis. In recent years, abnormal expression of SOCS‐3 and its multiple functions have been extensively investigated in human carcinomas, particularly in prostate cancer. SOCS‐3 can act as an oncogene or a tumor suppressor depending on the cellular context. In this review, we focus on the role of SOCS‐3 in prostate cancer development and prognosis, as well as the potential of SOCS‐3 as a therapeutic target and diagnostic marker.